2019
DOI: 10.2337/dc19-1425
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes From the English National Health Service Diabetes Prevention Programme

Abstract: To assess weight and HbA 1c changes in the Healthier You: National Health Service Diabetes Prevention Programme (NHS DPP), the largest DPP globally to achieve universal population coverage. RESEARCH DESIGN AND METHODS A service evaluation assessed intervention effectiveness for adults with nondiabetic hyperglycemia (HbA 1c 42-47 mmol/mol [6.0-6.4%] or fasting plasma glucose 5.5-6.9 mmol/L) between program launch in June 2016 and December 2018, using prospectively collected, national service-level data in Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(197 citation statements)
references
References 17 publications
8
186
0
Order By: Relevance
“…At the same time, there has been progress in diabetes prevention. Early examination of the English diabetes prevention programme shows good weight loss in individuals adhering to the programme but improvements in program engagement, retention and completion are required 13 . Currently, the focus of these programmes is to identify those at highest risk and introduce lifestyle changes to slow or halt progression to diabetes.…”
Section: Trends In Cardiovascular and Diabetes Prevalence \mentioning
confidence: 99%
“…At the same time, there has been progress in diabetes prevention. Early examination of the English diabetes prevention programme shows good weight loss in individuals adhering to the programme but improvements in program engagement, retention and completion are required 13 . Currently, the focus of these programmes is to identify those at highest risk and introduce lifestyle changes to slow or halt progression to diabetes.…”
Section: Trends In Cardiovascular and Diabetes Prevalence \mentioning
confidence: 99%
“…The combination of dietary modification and exercise also reduced the number of microvascular complications (by 35%), cardiovascular deaths (by 33%), cardiovascular disease events (by 26%) and all‐cause deaths (by 26%), while increasing average life expectancy by 1.44 years . A systematic review commissioned by Public Health England to inform the design of the NHS DPP found that lifestyle interventions reduced weight by an average 2.5kg, HbA 1c by 0.8mmol/mol and T2D incidence by 26% compared with usual care …”
Section: Robust Evidencementioning
confidence: 99%
“…An intention‐to‐treat analysis reported a mean weight loss of 2.3kg and an HbA 1c reduction of 1.26mmol/mol. Among participants who completed the programme, defined as attending more than 60% of sessions, mean weight loss was 3.3kg with an HbA 1c reduction of 2.04mmol/mol …”
Section: Robust Evidencementioning
confidence: 99%
See 2 more Smart Citations